Trends in sports-related emergency department visits in the Netherlands, 2009–2018 - Vincent Gouttebarge; Evert Verhagen; Branko F Olij; Ellen Kemler; Huib Valkenberg; Christine Stam (BMJ Open Sport & Exercise Medicine)
Objectives We aim to describe time trends of severe sports-related emergency department (ED) visits in the Netherlands, from 2009 to 2018.Methods Data were extracted from the Dutch Injury Surveillance System by age, gender, sports activity and injury diagnosis, from 2009 to 2018. Absolute numbers and time trends of severe sports-related ED visits were calculated.Results Between 2009 and 2018, the overall numbers of severe sports-related ED visits in the Netherlands have significantly decreased by 14% (95% CI −19% to −9%). This trend was seen among men (−12%; 95% CI −18% to −6%), women (−19%; 95% CI −26% to −11%) and individuals aged 18–34 years (−19%; 95% CI −28% to −10%). The number of ED visits has significantly decreased over time in soccer (−15%; 95% CI −24% to −6%), ice-skating (−80%; 95% CI −85% to −73%) and in inline/roller skating (−38%; 95% CI −55% to −15%). This was not the case in road cycle racing (+135%; 95% CI +85% to +198%) and mountain bike racing (+80%; 95% CI +32% to+146%). In terms of sports injury diagnoses, the number of fractured wrists (−15%; 95% CI −24% to −5%), fractured hands (−37%; 95% CI −49% to −21%), knee distortions (−66%; 95% CI −74% to −55%), and fractured lower legs (−38%; 95% CI −55% to −14%) significantly decreased over time.Conclusion Our study shows a promising reduction in the number of severe sports-related ED visits across most age groups and sports activities. As the number of ED visits increased in road cycle and mountain bike racing, it is important to find out what caused these increases. Furthermore, it is essential to determine trends in exposure hours and to evaluate and implement injury prevention programmes specific for these sports activities.